REFLECTION ON ACCOUNTABILITY IN NYADRAN CULTURE - Nasyi’ah, Eny Zuhrotin; Nandiroh, Umi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study aims to explore the understanding of accountability within the Nyadran tradition in Karangsari Village, Ngawi District, East Java Province. The research adopts a qualitative approach with a phenomenological method, focusing on gaining a deep understanding of the subjective experiences of the participants involved in Nyadran. Data were collected through in-depth interviews, participatory observation, and document analysis, involving eight informants, including traditional leaders, religious figures, and active participants in the Nyadran ceremony. The findings reveal that accountability in Nyadran is reflected in the transparency of resource management, active participation, and collective responsibility throughout the ritual process. Additionally, the concept of accountability in Nyadran encompasses social, cultural, and spiritual dimensions, where the community feels responsible not only to one another but also to their ancestors and God. The study also highlights the importance of open communication, collaboration, and deliberation in ensuring the smooth execution of Nyadran. Suggestions for future research include expanding the study of accountability in other traditional cultures and exploring the role of technology in enhancing transparency and participation in cultural practices in the modern era. Future studies may also examine the younger generation's understanding of accountability in local traditions and their adaptation to changing times.